Isolation and identification of Streptomyces sp. and assay of its exocellular water-soluble blue pigments - Lu, Ling; Cui, H L; Chen, Y N; Yuan, S (Folia microbiologica, 2002)
A bacterial strain producing a great amount of blue pigment during submerse fermentation was isolated and identified. Based on morphological characteristics, cell-wall chemotype and sequence of 16S rRNA gene, the strain should belong to the genus Streptomyces; it had 99.4% homology of 16S rRNA gene sequence with that of Streptomyces indigocolor. The pigment production by the strain was affected by carbon and nitrogen sources. The main components of the pigment mixture (detected by HPLC and TLC) were tentatively classified as actinorhodin-related compounds. The pigment was relatively stable against light and higher temperature but was sensitive to low pH. The preliminary acute-toxicity determination showed that the pigment was nontoxic (LD50 > 15 mg/g).
Keywords: geny rRNA; DNA, Ribosomal; Sequence Analysis, DNA; Molecular Sequence Data; molekulární sekvence - údaje; Genes, rRNA; RNA ribozomální 16S; rozpustnost; zvířata; biologické pigmenty; myši; RNA, Ribosomal, 16S; Mice; sekvenční analýza DNA; Pigments, Biological; půdní mikrobiologie; Solubility; ribozomální DNA; Bacterial Typing Techniques; buněčná stěna; Animals; Cell Wall; techniky typizace bakterií; Streptomyces; Soil Microbiology